2019
DOI: 10.14309/01.ajg.0000591848.50785.d5
|View full text |Cite
|
Sign up to set email alerts
|

579 The Efficacy and Safety of Andexanet Alfa in Patients With Acute Gastrointestinal Bleeding While Taking Factor Xa Inhibitors: An ANNEXA-4 Sub-Analysis

Abstract: INTRODUCTION: Andexanet alfa is a recombinant modified human Factor Xa (FXa) decoy protein developed to reverse the anticoagulant effect of FXa inhibitors. METHODS: ANNEXA-4 was a prospective single-arm study of andexanet alfa in patients with acute major bleeding while taking a FXa inhibitor. Patients with major gastrointestinal (GI) bleeding were eligible if they had (1) signs/symptoms of hemodynamic compromise or (2) bleeding associated with a hemogl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…Overall, there are limited data regarding all‐cause mortality and specific causes of death after major OAC‐associated GI bleeding in contemporary studies. In OAC reversal studies and observational cohorts, 30‐day all‐cause mortality after OAC‐associated major GI bleeding is 11%–13% 6,7,17,41,52 . For example, in the RE‐VERSE AD and ANNEXA‐4 studies, all‐cause mortality among patients presenting with acute major GI bleeding was 11% and 13%, respectively, despite the treatment with agents that reversed anticoagulant effect and reduced levels of active drug 6 …”
Section: Outcomes After Oac‐associated Gi Bleeding and The Influence Of Oac Resumptionmentioning
confidence: 99%
See 4 more Smart Citations
“…Overall, there are limited data regarding all‐cause mortality and specific causes of death after major OAC‐associated GI bleeding in contemporary studies. In OAC reversal studies and observational cohorts, 30‐day all‐cause mortality after OAC‐associated major GI bleeding is 11%–13% 6,7,17,41,52 . For example, in the RE‐VERSE AD and ANNEXA‐4 studies, all‐cause mortality among patients presenting with acute major GI bleeding was 11% and 13%, respectively, despite the treatment with agents that reversed anticoagulant effect and reduced levels of active drug 6 …”
Section: Outcomes After Oac‐associated Gi Bleeding and The Influence Of Oac Resumptionmentioning
confidence: 99%
“…Among patients receiving idarucizumab for dabigatran reversal in the RE‐VERSE AD study, 30‐day and 90‐day rates of thrombotic events were 2.9% and 4.4%, respectively (Table 3); two thirds of these cases occurred in absence of OAC resumption. In the ANNEXA‐4 study assessing andexanet alfa for reversal of factor Xa inhibitors, the 30‐day risk of thromboembolism was 6% 6 . Further, Qureshi et al reported 17% risk of thromboembolism within 1 year of major GI bleeding in an AF population with median CHADS 2 score of 3 46 .…”
Section: Outcomes After Oac‐associated Gi Bleeding and The Influence Of Oac Resumptionmentioning
confidence: 99%
See 3 more Smart Citations